Seismic behavior of unbonded post-tension wall with replaceable energy dissipator. Issue 166 (March 2023) - Mi, Peng; Tan, Ping; Li, Yiming; Zhao, Xiaofeng; Tang, Mengxiong
Abstract: Unbonded post-tension (UPT) precast concrete shear walls achieve better recentering capacity with little residual drift but less energy dissipation capability. To improve the situation, a steel-reinforced UPT precast concrete wall with replaceable low-yield-point steel plates as energy dissipators (PEWs) is developed. The proposed wall is a load bearing-energy dissipation dual function system with two seismic lines of defense. A design approach is proposed to determine the damper force under a certain energy-dissipation moment ratios. The wall behavior is analyzed concerning four performance states under combined gravitational and lateral loads using an elaborate fiber model developed in OpenSsees. Lateral bearing yield strength and peak resistance increased under monotonic and cyclic loading respectively. All the relative energy-dissipation ratios of the PEW at different cycles are greater than 0.125, as recommended by ACI ITG T5.1. The performances of two eight-story frame shear wall structures with and without energy dissipators devices subjected to 22 the maximum considered earthquake records are compared. The base shear forces, roof displacement response and story drift of the PEW reduced significantly. The PEW specimens exhibited superior behavior in terms of lateral resistance and energy dissipation. Highlights: Steel-reinforced unbonded post-tension precast concrete wall with Low yield steel dissipators is proposed. Design method and the analytic fiber model of the wall are proposed. The seismic behavior of the wall is evaluated with different behavior states. Proposed wall system shows high lateral resistance and energy dissipation through nonlinear time-history analyses.